Smart Cards: The Developer's Toolkit - Jurgensen, Timothy; Guthery, Scott (Pearson, 2002)
The complete smart card guidebook for decision-makers, product managers, developers, and integrators. Smart card application development from start to finish: design, development, and deployment Covers every component of a complete system: cards, readers, host software, management systems, and more Focuses on advanced "post issuance programmable" multi-application smart cards Presents detailed case studies and product coverage Offers up-to-the-minute insights into the evolving smart card marketplace and smart card technology Smart cards represent a breakthrough solution for maximizing security in a wide range of applications. Now, two leading smart card consultants present a thorough, up-to-date, accessible introduction to smart card technology that will be invaluable to developers and decision-makers alike. Smart Cards: A Developer's Toolkit covers all you need to know to plan, design, develop, and deploy advanced multi-application smart card environments, including: Smart card physical structure, construction, tamper resistance, and tamper-evident features International standards, inter-industry command sets, and industry specifications "Post issuance programmable" smart cards: the cutting edge of smart card deployment An in-depth review of two "high-performance" smart cards, including one multi-application card PC and workstation host software for supporting smart cards Applications with the SIM smart cards in GSM and 3G mobile phones Card management systems and readers for large-scale applications in real-world environments The evolving marketplace for smart cards in the U.S. and worldwide The authors present case studies from today's most advanced smart card deployments, covering both the logistics of initial deployment and best practices for supporting ongoing operations and card populations. Whether you're an IT manager, corporate security officer, product manager, developer, or integrator, Smart Cards: A Developer's Toolkit gives you a powerful new weapon for protecting your digital assets.